Pengaruh Motivasi dan Pengetahuan UU No.5 Tahun 2011 Pada Minat Mahasiswa Akuntansi Mengikuti PPAK - Febryanti A, Putu Ayu Bella; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
Importance of Accounting Profession Education for accounting students hence required motivation in student to interest to follow Professional Accounting Education. This study aims to obtain empirical evidence on the influence of career motivation, motivation to follow USAP, quality motivation, economic motivation, and knowledge of Law no. 5 Year 2011 on public accountants on the interest of accounting students follow Accounting Profession Education (PPAk). Research respondents are students of non-regular program of class of 2014, Faculty of Economics and Business Universitas Udayana, which is 185 students. The sample is determined using a saturated sample. The method of data collection is by survey. Data were analyzed by multiple linear regression. The result of analysis shows that the higher motivation of career, motivation to follow USAP, motivation of quality, economic motivation hence higher also interest to follow PPAk, and the higher knowledge of accounting student about Law no. 5 Year 2011 hence the higher also the interest of accounting student follow PPAk.   Keywords: career motivation, motivation to follow swab, quality motivation, economic motivation, knowledge uu no. 5 about public accountant, accounting student interest follow ppak.